Critical Academy under Attack - Gavan Titley; Sahana Udupa; Éric Fassin; Diana Mulinari (Media Theory)
Scholars working within different critical theory traditions are not unfamiliar with the experience of encountering dismissive representations of their work, including from parts of the academy that disavow the politics of academic research and knowledge production. However, the political project of delegitimizing critical research and scholarship seems to be intensifying. Signifiers like “critical theory”, “critical race theory” and “gender theory” have become objects of antagonism and moral panic for a diverse cast of political, cultural and media actors, including self-styled academic dissidents with audiences well beyond the academy. In tandem, critical scholarship faces an increasingly inhospitable ecology within the neoliberal university, even while the latter simultaneously brands itself in the language of social justice. Chaired and introduced by Gavan Titley, the panel contributions from Sahana Udupa, Éric Fassin, and Diana Mulinari reflect on the challenges faced by critical scholars and critical scholarship in a time of emboldened reactionary politics. It asks how these challenges might be intellectually and politically confronted, and countered, in light of the special issue’s reflections on the current condition of critique.